Integration, mobility, and human capital formation - Alexander Haupt; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this note, we show that labour market integration can be a double-edged sword. In the presence of local human capital externalities, integration and the ensuing agglomeration of skilled labour can cause a decline in human capital and the total wage sum (net of education costs). In particular, integration depresses the incentives for some talented but immobile individuals to become skilled.
Keywords: F22; J24; J61; R23; 330; human capital; migration; labour market integration; agglomeration; Humankapital; Regionale Arbeitsmobilität; Berufliche Integration; Agglomerationseffekt; Externer Effekt; Bildungsinvestition; Theorie